2020
DOI: 10.1021/acsomega.9b03510
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maleimide Disubstitution on Chemical and Biological Characteristics of HER2 Antibody–Drug Conjugates

Abstract: Antibody−drug conjugates (ADCs) are the spearhead of targeted therapies. According to the technology used, the conjugation of a cytotoxic drug to an antibody can produce suboptimal heterogeneous species, impacting the overall efficacy. Herein, we describe the synthesis of HER2targeting ADCs with three disulfide rebridging heads, allowing homogeneous and site-specific bioconjugation: dibromomaleimide (DBM), dithiomaleimide (DTM), and hybrid thiobromomaleimide (TBM) chemical bricks to combine the properties of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…16,31 B HIC Analysis. Samples of 50 μg were analyzed at 280 nm as previously described 36 on a MAbPac HIC-butyl, 5 μm, 4.6 × 100 mm column (ThermoScientific), and eluted with a step gradient over 30 min at 1 mL/min, at 25 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,31 B HIC Analysis. Samples of 50 μg were analyzed at 280 nm as previously described 36 on a MAbPac HIC-butyl, 5 μm, 4.6 × 100 mm column (ThermoScientific), and eluted with a step gradient over 30 min at 1 mL/min, at 25 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…E SEC Analysis. Samples of 50 μg were analyzed at 280 nm as previously described, 36 on an AdvanceBio SEC 2.7 μm, 7.8 × 300 mm column (Agilent Technologies), and eluted with an isocratic gradient (PBS pH 7.0, 0.02% sodium azide) over 24 min at 1 mL/min, at 25 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…135 Furthermore, Feuillâtre et al reported the use of hybrid thiobromomaleimides (TBMs) which were shown to produce homogenous ADCs with a marginally narrower DAR distribution compared to dibromomaleimide and dithiophenolmaleimide reagents. 136 NGMs have repeatedly demonstrated the ability to generate ADCs with high levels of homogeneity. Optimisation of the ring hydrolysis has significantly improved the utility of this method and allowed for the synthesis of ADCs with excellent plasma stability.…”
Section: Disulfide Rebridgingmentioning
confidence: 99%
“…They lead to the substitution with the two nucleophilic thiol groups and enable better stability compared to classic maleimides, which are prone to retro-Michael reaction. Recently it was reported the synthesis of hybrid thiobromomaleimide (TBM) combining the properties of dibromo- and dithiomaleimide [ 112 ]. This TBM reagent conjugates faster and demonstrates higher percentage of DAR 4 probably due to the bromide that reduces steric hindrance and represents a better living group than the thiophenolate.…”
Section: Bioconjugationmentioning
confidence: 99%